BIOLO.GIA - Atoche Suclupe, Dennis Elthon (2011)
The characteristics of the Biology and Fishery of Ethmidium maculatum "machete"_x000D_ coming from the artisanal fishing in the Region La Libertad were determined during the_x000D_ 2010. The database was constituted by 1508 individuals, obtained at random of the_x000D_ landings of Caleta Puerto Morín, Puerto Salaverry, Caleta Huanchaco, Puerto Malabrigo_x000D_ and Puerto Pacasmayo. For the biological analysis, it was considered maximum 10_x000D_ individuals by size class. To determine the food and alimentary habits were carried out_x000D_ analysis of percentage estimate and occurrence frequency; to determine the reproductive_x000D_ characteristics, the stages of maturity gonadal and index Gonadosomático were_x000D_ analyzed; the grade of well-being was determined, by means of the factor of condition_x000D_ of Fulton; the constants of growth were calculated using the software FISAT Il. The_x000D_ mean size of capture was inferior to the established legal minimum size. This species_x000D_ was tipifyed in the study as zooplanktonophagous. The sexual proportionwast favorable_x000D_ to the females; the stage desovante prevailed and the species spawns with more intensity at the end of winter. The growth for females and males was allometric. A volume of landing of 26 779 kg was reported, and the main fishing areas were: Chao, El Carmelo, Buenos Aires, Las Delicias, Salaverry, Los Brujos and Huanchaco. The relationship among effort, captures and catch per unit of effort, showed a possible stability in the machete fishery. It is concluded that this species is still stable relative abundance levels; however it is necessary to establish regulation measures.